2008
DOI: 10.1002/cncr.23583
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes for elderly patients treated with weekly paclitaxel in combination with carboplatin versus the standard 3‐weekly paclitaxel and carboplatin for advanced nonsmall cell lung cancer

Abstract: BACKGROUND.The purpose of this study was to compare the outcomes between elderly (aged ≥70 years) patients treated with paclitaxel on a weekly basis and with carboplatin (every 4 weeks) versus the standard 3‐weekly regimen of carboplatin and paclitaxel for first‐line therapy of advanced nonsmall cell lung cancer.METHODS.Of the 444 patients enrolled, 136 (31%) were aged ≥70 years. Seventy‐two patients were randomized to the weekly schedule (paclitaxel, 100 mg/m2 weekly for 3 of 4 weeks; carboplatin, area under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…These findings incorporated with the results of Suresh et al 28 and Sakakibara et al 29 Although the differences in the duration of treatment cycle between the two arms (4 and 3 weeks, respectively, for arms 1 and 2) could have contributed to differences in median TTP, the overall survival and 1-year survival results are comparable between the two arms. The lower incidence of grade 2/3 neuropathy was achieved with the weekly paclitaxel regimen despite the same doseintensity of paclitaxel on both the arms.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These findings incorporated with the results of Suresh et al 28 and Sakakibara et al 29 Although the differences in the duration of treatment cycle between the two arms (4 and 3 weeks, respectively, for arms 1 and 2) could have contributed to differences in median TTP, the overall survival and 1-year survival results are comparable between the two arms. The lower incidence of grade 2/3 neuropathy was achieved with the weekly paclitaxel regimen despite the same doseintensity of paclitaxel on both the arms.…”
Section: Discussionsupporting
confidence: 75%
“…Although the regimen is well tolerated, it is associated with a 10% to 17% incidence of neuropathy [25][26][27] . Suresh et al 28 reported overall response rate of 19%, median survival duration of 31 weeks and 1-year survival rate of 33% and grade 3 neuropathy of 9.5% with 3-weeks paclitaxel and carboplatin in elderly patients with advanced NSCLC. Sakakibara et al 29 reported an overall response rate of 53% and median progression-free survival of 5.6 months and grade 3/4 neuropathy of 25% with 3-week paclitaxel and carboplatin in elderly patients with advanced NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous phase II studies have evaluated platinum-doublet chemotherapy, mostly with modified schedules, such as low doses or weekly administration [24,25,26,27,28]. Additionally, a recent phase III study has shown that platinum-based doublet chemotherapy with carboplatin and weekly paclitaxel yield better results than monotherapy with either vinorelbine or gemcitabine in terms of overall survival, PFS and response rates in elderly patients with advanced NSCLC [10].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent phase III study has shown that platinum-based doublet chemotherapy with carboplatin and weekly paclitaxel yield better results than monotherapy with either vinorelbine or gemcitabine in terms of overall survival, PFS and response rates in elderly patients with advanced NSCLC [10]. In these studies or subset analyses of randomized phase III trials without upper age limits, response rates have ranged from 23 to 52%, MSTs have ranged from 7 to 14 months, and median PFS has ranged from 4.3 to 8 months [7,8,9,10,24,25,26,27,28]. In the present study, the response rate was 45.7%, the MST was 14 months, and the median PFS was 5 months.…”
Section: Discussionmentioning
confidence: 99%
“…Its safety profile, in particular, is the greatest strength that may benefit elderly patients with less tolerance to chemotherapy. Recently, Ramalingam et al [18] reported the results of subset analysis from Belani's study specifically targeted for elderly population. Very similar to our study, they also concluded that regimen with weekly paclitaxel was equally effective and less toxic than that with standard paclitaxel in the elderly population, although the response rate of weekly regimen was less than that in our study (26% versus 55%).…”
Section: Discussionmentioning
confidence: 99%